2018
DOI: 10.1002/jcb.27273
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of curcuminoids in improvement of ulcerative colitis symptoms and patients’ self‐reported well‐being: A randomized double‐blind controlled trial

Abstract: Adding curcuminoids nanomicelles to routine treatment of patients with ulcerative colitis is associated with a significant improvement of symptoms, including reduced frequency of urgent defecation, improved patients' self-reported well-being and reduced clinical activity of ulcerative colitis. ClinicalTrials. "IRCT2017052634142N1".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 35 publications
1
77
0
1
Order By: Relevance
“…Lang et al () showed that 1‐month supplementation with 3 g/day curcumin was effective in inducing the clinical and endoscopic remission in patients with mild‐to‐moderate active UC. A randomized controlled trial by Masoodi et al () reported that the mean SCCAI score was significantly lower in patients who took 240 mg of curcuminoids nanomicelles in addition to mesalamine compared with the control group. On the contrary, Kedia et al () showed that supplementation with curcumin could not improve the clinical outcomes, such as clinical remission, clinical response, and mucosal healing in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lang et al () showed that 1‐month supplementation with 3 g/day curcumin was effective in inducing the clinical and endoscopic remission in patients with mild‐to‐moderate active UC. A randomized controlled trial by Masoodi et al () reported that the mean SCCAI score was significantly lower in patients who took 240 mg of curcuminoids nanomicelles in addition to mesalamine compared with the control group. On the contrary, Kedia et al () showed that supplementation with curcumin could not improve the clinical outcomes, such as clinical remission, clinical response, and mucosal healing in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin and the whole turmeric rhizome have some beneficial effects in the treatment of chronic diseases such as gastrointestinal, cardiovascular, and neurological disorders, diabetes, and several types of cancer [31][32][33][34][35]. Clinical trials based on curcumin administration have been published or are currently in progress, pointing out the expanding interest of the scientific community on the therapeutic potential of curcumin [36][37][38][39].…”
Section: Curcumin: Metabolism and Bioavailabilitymentioning
confidence: 99%
“…The clinical improvement, which was defined as a reduction of UCDAI ≥ 3 or SCCAI ≥ 3, has no significant difference between curcumin and placebo. But Masoodi et al ., the trial included for systematic review, showed that the mean SCCAI score was significantly lower in the patients who received curcumin compared with placebo after 4 weeks of treatment (1.71 ± 1.84 vs 2.68 ± 2.09, P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a polyphenol derived from the turmeric plant ( Curcuma longa ), has been demonstrated to hold many health‐related benefits and pharmacological effects, including anti‐inflammatory, antibacterial actions, and improving symptoms of auto‐immune diseases . Adjuvant use of curcumin in UC has become quite common recently . Multiple animal and human studies suggested that the anti‐inflammatory effect of curcumin in UC was primarily mediated by inhibiting the inflammatory pathways and mediators, such as NF‐κB and TNF‐α .…”
Section: Introductionmentioning
confidence: 99%